Les lois d’amnistie devant la Cour européenne des Droits de l’Homme - Amane Gogorza (Criminocorpus)
Although it is more limited and less emblematic than the case dealt with by the IACHR, amnesty litigation before the European courts nonetheless allows us to take account of important developments that are mainly due to the erosion of sovereignty and the influence of fundamental rights in the treatment of forgetting and/or forgiveness. After some hesitation, a point of equilibrium seems to be emerging in the light of the fight against impunity and the corresponding sidelining of mechanisms hindering the investigation, prosecution and punishment of massive human rights violations. Unlike its counterpart on the other side of the Atlantic, however, the ECHR has never completely closed the door on amnesty laws, whose validity could well be accepted on condition that they are part of a process of social reconciliation.